Question Number 100986 by Dwaipayan Shikari last updated on 29/Jun/20

Commented bybachamohamed last updated on 29/Jun/20

look this   2=(√(1+(√9)))=(√(1+(√(1+8))))=(√(1+(√(1+(√(64))))))=(√(1+(√(1+(√(1+63))))))    =(√(1+(√(1+(√(1+(√(63^2 ))))))))=(√(1+(√(1+(√(1+(√(1+(63^2 −1)))))))))  =(√(1+(√(1+(√(1+(√(1+(√(((63^2 −1))^2 ))))))))))=(√(1+(√(1+(√(1.....+(√(1........∞))))))))  3=(√9)=(√(1+(√(64))))=(√(1+(√(1+63))))=(√(1+(√(1+(√(63^2 ))))))=(√(1+(√(1+(√(1+(√(1......∞))))))))  4=(√(16))=(√(1+15))=(√(1+(√(225))))=(√(1+(√(1+224))))=(√(1+(√(1+(√(224^2 ))))))=(√(1+(√(1+(√(1...(√(....(√(1...∞))))))))))  donc pour tout nombre posituve n  n=(√(1+(√(1+(√(1+(√(1.....∞))))))))  why?